161k views
5 votes
Solve the system of equations y=2x y=x^2-3

2 Answers

4 votes
if x = 3, y = 6
if x = -1, y = -2
hope it help :)
User Mosaaleb
by
5.9k points
4 votes

Answer:

Explanation:

we can use the substitution method to solve this system of equations .

Substitute y= 2x in second equation y= x^2-3

we get


2x=x^2-3\\x^2-2x-3=0

Now factor the equation


(x-3)(x+1)=0\\x-3=0 \\x+1=0

We get

x=3 and x=-1

for x=3 y=2(3)=6

and for x=-1

y=2(-1)=-2

solution is

(3,6) and (-1,-2)

User Joe Daley
by
5.3k points